PENGEMBANGAN SISTEM INFORMASI DATA CENTER SEBAGAI PENYEDIA DATA PENYUSUNAN BORANG AKREDITASI - Atin Triwahyuni (Telematika, 2014)
Accreditation is a method of evaluating programs and policies of a college to ensure that the program of study at a college meet certain criteria, which are usually set by the institution / agency accreditation. The problem that often arises is the lack of information that provides a neatly arranged accreditation forms of data compilation. This research is important to do, because it helps reduce data recording repeated in the preparation of the accreditation forms and can speed up the process of preparing the accreditation forms by providing a data center that is packed in an information system. The results showed that the presence of information systems data center accreditation forms can correct accreditation forms of data processing and documentation neat. With the help of the form of office automation system can produce output in the form of a Microsoft Excel file that will facilitate in developing the necessary data in the preparation of the accreditation forms.